Relationship between physicians with drug companies and ethics [Hekimlerin ilaç firmalariyla ilişkileri ve etik] - (:unkn) unknown (My University, 2005)
Gifts from drug companies to physicians are ubiquitous, ranging from pens, watches, umbrellas, books and magazines, to meals at conferences. Drug companies frequently provide lunch or refreshments at conferences. They may support conferences by paying money and travel expenses for speakers. Some drug companies cover physicians travel expenses to attend meetings. Physicians often accept gifts from drug companies. As profit making companies, drug companies emphasize the recognition of their products through gifts bearing the drug's name. Many physicians consider it absurd to believe the gifts from drug companies which might effect the doctors' decisions about patients'care adversely. They are insulted at the suggestion in that accepting gifts might impair their clinical judgment.